NILAI-NILAI PLURALISME DALAM PENDIDIKAN ISLAM: BELAJAR DARI KEBERAGAMAN QIRA'AT 'ASYR - Dana Akhmad Dahlani; Abdul Muhid (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
The study of Qira'at 'Asyr is highly recommended for students who wish to comprehend the implicit diversity in the Qur'an. Using a comprehensive approach to this discipline, students must be active and proactive to serve as "primary agents" in the learning process, and build skills and comprehension of a sacred text, particularly regarding the diverse values included within a verse. Due to the textual and conservative religious understanding of sacred religious scriptures, religious radicalism has begun to surface. Acquiring this knowledge is likely to mitigate this phenomenon. Using descriptive analysis, this essay will investigate the values of pluralism in the learning tradition of 10 varieties of Al-Qur'an readings in greater depth.